Neural Working Memory Changes During a Spaceflight Analog With Elevated Carbon Dioxide: A Pilot Study - Salazar, Ana Paula; Hupfeld, Kathleen E.; Lee, Jessica K.; Beltran, Nichole E.; Kofman, Igor S.; De Dios, Yiri E.; Mulder, Edwin; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Seidler, Rachael D. (Frontiers in Systems Neuroscience, 2020)
Spaceflight missions to the International Space Station (ISS) expose astronauts to microgravity, radiation, isolation, and elevated carbon dioxide (CO2), among other factors. Head down tilt bed rest (HDBR) is an Earth-based analog for spaceflight used to study body unloading, fluid shifts, and other factors unrelated to gravitational changes. While in space, astronauts need to use mental rotation strategies to facilitate their adaptation to the ISS environment. Therefore, spatial working memory is essential for crewmember performance. Although the effects of HDBR on spatial working memory have recently been studied, the results are still inconclusive. Here we expand upon past work and examine the effects of HDBR with elevated CO2 (HDBR+CO2) on brain activation patterns during spatial working memory performance. In addition, we compare brain activation between 30 days of HDBR+CO2 and 70 days of HDBR to test the isolated effect of CO2. Eleven subjects (6 males, 5 females; mean age = 34 ± 8 years) underwent six functional magnetic resonance imaging (fMRI) sessions pre-, during, and post- HDBR+CO2. During the HDBR+CO2 intervention, we observed decreasing activation in the right middle frontal gyrus and left regions of the cerebellum, followed by post-intervention recovery. We detected several correlations between brain and behavioral slopes of change with the HDBR+CO2 intervention. For example, greater activation increases in frontal, temporal and parietal regions was associated with larger spatial working memory improvements. Comparing the HDBR+CO2 group to data from our previous 70-day HDBR study, we found greater decreases in activation in the right hippocampus and left inferior temporal gyrus for the HDBR+CO2 group over the course of the intervention. Together, these findings increase our understanding of the neural mechanisms of HDBR, elevated levels of CO2 and spaceflight-related changes in spatial working memory performance.